Fertility Effects of College Education: Evidence from the German Educational Expansion - Daniel Kamhoefer; Matthias Westphal (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
We estimate the effects of college education on female fertility - a so far understudied margin of education, which we instrument by arguably exogenous variation induced through college expansions. While college education reduces the probability of becoming a mother, college-educated mothers have slightly more children than mothers without a college education. Unfolding the effects by the timing of birth reveals a postponement that goes beyond the time in college - indicating a negative early-career effect on fertility. Coupled with higher labor-supply and wage returns for non-mothers as compared to mothers the timing effects moreover suggest that career and family are not fully compatible.
Keywords: C31; H52; I21; J12; J13; 330; Fertility; family planning; education